Patient reported experience of inpatient rehabilitation in Australia - Jacquelin Capell (The Beryl Institute, 2020)
While the value of patient reported experience is increasingly acknowledged, the measurement of rehabilitation-specific patient reported experiences is an area that is yet to attract a lot of attention. The aim of this study was to examine the patient-reported experience of person-centred inpatient rehabilitation. The study consisted of a multi-site cross sectional survey using the 33-item modified Client Centred Rehabilitation Questionnaire (CCRQ). A total of 408 participants were recruited from 20 inpatient rehabilitation facilities across Australia. Participants were in the final days of their inpatient rehabilitation episode when approached to complete the paper based modified CCRQ. Nineteen of the 33 items had an 80% or greater proportion of positive responses (‘agree’, ‘strongly agree’). The items belonging to the Family Involvement and Support subscale had the lowest proportion of positive responses (range 57.1%-82.4%), the highest proportion of ‘does not apply’ responses (range 10.0%-23.0%) and the largest variability in positive responses across all 33 items. The three negatively worded items (items 2 and 33 in the Client-centred Education subscale and item 7 from the Continuity/Co-ordination subscale) demonstrated the greatest proportions of negative responses (range 44.6%-65.7%). The breadth of the modified CCRQ items enables identification of service gaps as seen from the patient’s perspective. Identification of such gaps allows rehabilitation services to plan actions to improve the quality of services provided. Experience Framework This article is associated with the Patient, Family & Community Engagement lens of The Beryl Institute Experience Framework. (http://bit.ly/ExperienceFramework) <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Patient%2C%20Family%20%26%20Community%20Engagement%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens.